The Influence of internet addiction, advertising appeal, and price discounts on impulsive online buying behavior of fashion products - Nova Mulyasari; Yuli Asbar; Widyana Verawaty Siregar (Operations Management and Information System Studies, 2021)
The study aims to analyze the influence (internet addiction, advertising appeal, and price discounts) on the impulsive buying behavior of online fashion products. This type of research is quantitative. Data collection is done by questionnaire method. The population in this study was all female consumers in North Aceh regency who had shopped for fashion products online. Samples are selected using the purposive sampling method. The number of samples in this study was 100 respondents. The results of the study obtained using multiple linear regression analysis techniques processed with the help of the SPSS version 18 computer program, namely Internet Addiction, Price Discount, partially significantly affect online impulsive buying behavior, Partial Ad Attractiveness has no significant effect on online impulsive buying behavior, and simultaneously the three independent variables (Internet Addiction, Internet Addiction, The attractiveness of advertising, and price discounts) significantly affects impulsive buying behavior online.